The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.3892/etm.2016.3203
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between brain natriuretic peptide levels and the prognosis of patients with left ventricular diastolic dysfunction

Abstract: Abstract. The present study aimed to investigate the association between brain natriuretic peptide (BNP) levels and the prognosis of patients with left ventricular (LV) diastolic dysfunction. A total of 708 inpatients with cardiovascular disease (mean age, 66 years; 395 males and 313 females) were grouped according to initial BNP and were followed-up for 20-51 months (average, 30.86 months) until endpoint events occurred. Endpoints were defined as mortality or readmission due to cardiovascular disease, or mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…On the other hand there is statistically significant negative correlation between BNP level and EF after 3 months; which indicated that increase in BNP level will be associated with decrease in EF [P-value < 0.01], and there was statistically significant difference in BNP level between degree of diastolic dysfunction with high mean BNP level among grade II diastolic dysfunction at presentation and after 3 months follow up [P-value < 0.05]. These findings were consistent with the work done in 2016 in a study [18]; named, Correlation between brain natriuretic peptide levels and the prognosis of patients with left ventricular diastolic dysfunction; that enrolled 708 patients who were followed up for 20-51 months. Endpoints were defined as mortality or readmission due to cardiovascular disease, or mortality due to any other reason.…”
Section: Aimsupporting
confidence: 83%
“…On the other hand there is statistically significant negative correlation between BNP level and EF after 3 months; which indicated that increase in BNP level will be associated with decrease in EF [P-value < 0.01], and there was statistically significant difference in BNP level between degree of diastolic dysfunction with high mean BNP level among grade II diastolic dysfunction at presentation and after 3 months follow up [P-value < 0.05]. These findings were consistent with the work done in 2016 in a study [18]; named, Correlation between brain natriuretic peptide levels and the prognosis of patients with left ventricular diastolic dysfunction; that enrolled 708 patients who were followed up for 20-51 months. Endpoints were defined as mortality or readmission due to cardiovascular disease, or mortality due to any other reason.…”
Section: Aimsupporting
confidence: 83%
“…Tanous, et al [17] explained that women with ventricular dysfunction correlates with high BNP during pregnancy. We postulate that her elevated BNP is attributed to renal impairment and persistently mild left ventricular impairement [18]. Long term prognosis for mortality, HF, and new ischemic events is described to be better stratified with a combination of NT ProBNP with LVEF [18,19].…”
Section: Discussionmentioning
confidence: 96%
“…B‐type natriuretic peptides is a peptide that assumes a crucial role in CHF compensatory response. It is secreted by ventricular myocyte in response to left ventricular volume expansion and pressure overload 4 . Since plasma BNP concentration raises during CHF, it is usually used as a biomarker for the diagnosis of this cardiovascular disease 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…It is secreted by ventricular myocyte in response to left ventricular volume expansion and pressure overload. 4 Since plasma BNP concentration raises during CHF, it is usually used as a biomarker for the diagnosis of this cardiovascular disease. 5,6 More specifically, according to the European Society of Cardiology (ESC) a BNP value higher than 100 pg/mL reflects the occurrence of CHF.…”
Section: Introductionmentioning
confidence: 99%